Refolding of triose phosphate isomerase - Waley, Stephen G. (1973)
The refolding and reactivation of the glycolytic enzyme triose phosphate isomerase (EC 5.3.1.1) has been studied. The enzyme, which is a dimer, is disaggregated and unfolded in solutions of guanidinium chloride. Unfolding, followed by changes in E(233), took place quite rapidly in 3m-guanidinium chloride (i.e. with a half-life of about 1 min). Refolding also took place rapidly when the solution was diluted about tenfold; two first-order processes could be resolved. Regain of enzymic activity was followed by diluting the solution of the denatured enzyme in guanidinium chloride into assay mixture. The half-life (i.e. the time when the activity was half the final activity) depended markedly on the concentration of protein at low concentrations (about 100ng/ml), but at higher concentrations the half-life became independent of concentration. Thus at low concentrations dimerization was a rate-determining step and this is taken to indicate that the monomers showed little or no activity under these conditions. The rate of regain of enzymic activity was the same as the rate of the slower process of refolding, which was detected spectroscopically. The native enzyme was resistant to proteolysis; high concentrations of subtilisin prevented regain of activity, but at lower concentrations refolding competed with proteolysis.